The Role of Bumdes (Village-Owned Enterprises) in Strengthening the Tourism Village Business Ecosystem: Sumberbulu Tourism Village Case Study - Permana, Odang; Sutono, Anang; Sumaryadi; Rahtomo, Wisnu; Ristanto, Hari (Archives of Business Research, 2023)
This study aims to identify business models and develop a model for strengthening BUMDES in managing tourism villages that are synergized in a value chain with related businesses in tourist villages (a case study in Sumberbulu Tourism Village, Karang Anyar Regency, Central Java, Indonesia). This study uses a descriptive method with a quantitative approach to identify BUMDES business models based on the tourism value chain and develop a model for strengthening the management of tourism villages that are synergized with businesses in a value chain with related businesses in tourism villages. This research was conducted in three stages, namely diagnosis, assessment by conducting a tourism value chain analysis conducted by BUMDES, and recommendations. This study found that in general, the role of BUMDES in maintaining the sustainability of the value chain in tourism business activities in Sumberbulu Tourism Village is quite good. However, there are several things, such as the quality of Human Resources in running the business and supporting facilities that still need to be improved